Thienothiophenyl‐Isoquinoline Iridium Complex‐Based Deep Red to Near‐Infrared Organic Light‐Emitting Diodes with Low Driving Voltage and High Radiant Emittance for Practical Biomedical Applications. Issue 10 (6th October 2021) - Park, Yongjin; Lee, Gyeong Seok; Choi, Hye-Ryung; Jeon, Yongmin; Jeong, So Yeong; Noh, Byeongju; Park, Kyoung-Chan; Kim, Yun-Hi; Choi, Kyung-Cheol
Abstract : Organic Light‐Emitting Diodes In article number 2100121, Kyung‐Cheol Choi, Yun‐Hi Kim, Kyoung‐Chan Park, and co‐workers develop a novel Ir(III)‐based deep red to near‐infrared (DR/NIR) emitter and demonstrate a highly reliable DR/NIR OLED with low driving voltage and high radiant emittance. In addition, the cell proliferation effect was confirmed by applying it to the bio field using the developed DR/NIR OLED for the first time.